A finTRIM member 100 (FTR100) is unique to Otomorpha fish for constitutive regulation of IFN response - Wen-Hao Guo; Cheng Dan; Xiu-Ying Gong; Yi-Lin Li; Hao-Yu Sun; Zi-Ling Qu; Li-Li An; Xiang Zhao; Jie Mei; Jian-Fang Gui; Yi-Bing Zhang (Water Biology and Security, 2023)
Vertebrate interferon (IFN) expression is fine-tuned in order to avoid excessive tissue injury under normal conditions and during virus infection. FinTRIM (fish novel TRIM, FTR) proteins are reported to regulate the fish IFN response. Here, we identify a novel finTRIM gene from yellow catfish (Pelteobagrus fulvidraco), which is sequentially named PfFTR100 according to the nomenclature rule in zebrafish. Genome-wide analyses reveal that FTR100 is unique to Otomorpha fish, with a single copy in spite of additional genome duplication in some fish species. Considering that few of the 99 finTRIM genes identified in zebrafish are conserved in main fish branches and most, such as FTR100, are unique to distinct branches due to lineage-specific expansion of finTRIM genes, we develop a nomenclature for newly cloned finTRIM genes from different fish species. PfFTR100 mRNA is not induced by virus infection, with a relatively high expression level comparable to that of cellular IFN and some IFN-stimulated genes (ISGs) in virally-infected tissues. However, ectopically-expressed PfFTR100 protein is attenuated in virally-infected cells through the proteasomal-dependent pathway. Overexpression of PfFTR100 promotes SVCV replication by downregulating the constitutive and inducible IFN response via a mechanism by which PfFTR100 targets IRF3 and IRF7 to attenuate their mRNA levels rather than their protein levels. Our results indicate that yellow catfish FTR100 is essential for homeostatic regulation of fish tonic IFN response.